Dermatologic Surgeons Can Positively Impact the Opioid Epidemic: A Quality Improvement Study of Pain Management in Dermatology Surgery. Issue 5 (May 2020) - Raji, Kehinde; Yeung, Howa; Bein, Amanda Ashley; Lequeux-Nalovic, Katarina G.
Abstract : BACKGROUND: The opioid epidemic is a national emergency, and it is imperative that all physicians are engaged in reducing exposure. Among dermatologists, dermatologic surgeons prescribe most opioids with the highest rates of prescription occurring in Southern states. OBJECTIVE: Implement a quality improvement intervention to decrease opioids prescribed and filled to <10% of surgeries performed and have a 0% increase in the amount of patient complaints regarding postoperative pain. MATERIALS AND METHODS: The number of opioids prescribed and filled in a single surgical facility in Georgia was obtained from the state's Prescription Drug Monitoring Program before, 1 month after, and 6 months after implementation of the quality improvement initiative. Telephone encounters regarding postoperative pain was also collected at the same specified periods. RESULTS: Proportion of opioids prescribed and filled decreased from 58% to 5% at 1-month postintervention and remained low on 6-month follow-up at 4%. There was no increase in postoperative pain complaints. Rather, a decrease in complaints was noted from 8.6% to 3.1% at 1-month postintervention and sustained on 6-month follow-up at 4.9%. CONCLUSION: Our data support the management of postoperative pain with nonopioid medications.